Israel : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Contents include: Budget deficit - concepts, measurements, and developments; definition, accounting basis, scope, and coverage. Structural reform issues: privatization; capital market reform; exchange and trade liberalization; other government intervention - investment subsidies and price controls; labor market reform; and land reform. Current account sustainability in Israel: overview of the Israeli economy and its transformation in the 1990s; a model of the current account applied to Israel; and sustainability indicators. Statistical tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet